201k views
3 votes
Factor 24x^3y^2-4x^2y+84x^4 please show work

1 Answer

3 votes

The given equation is :


24x^(3)y^(2) -4x^(2)y +84x^(4)

Now taking
4x^(2) common from all the terms, we get


4x^(2) (6xy^(2) -y+21x^(2) )=0

Writing the equation in standard form we get:


21x^(2) +6xy^(2) -y=0

Now we will use the formula of quadratic equations to solve this,


x1,2 = \frac{-b+\sqrt{b^(2)-4ac }} {2a} and


x1,2 = \frac{-b-\sqrt{b^(2)-4ac }} {2a}

Now putting a = 21, b = 6y² and c = -y and solving the equations, we get


x=\frac{-6y^(2)+\sqrt{36y^(4)+84y }}{42} and


x=\frac{-6y^(2)-\sqrt{36y^(4)+84y }}{42}

User Layton
by
4.8k points